Batang ina at ama: Pregnancy experiences, sexual behavior and attitudes of adolescents parents and the school-based services they would like to receive - Coballes, Pearl Via S. (Animo Repository, 2024)
This project explored the sexual behaviors, sexual attitudes and the difficult experiences of adolescent parents. It also sought their perceptions of the role their parents and their school with adolescent pregnancy and parenthood. A mixed method research design was utilized, particularly survey questionnaire, FGD and semi-structured questionnaire, to find out their sexual behavior and attitude, as well as their difficult experiences as adolescent parents. Participants were 10 male and 10 female adolescent parents who were attending a private Catholic university at the time of pregnancy. The findings revealed that adolescent parents’ sexual behavior is a spontaneous activity which they engaged without using any form of protection to prevent pregnancy. The pregnancy is unplanned but not unwanted and it is viewed as challenging but not regretful. Their sexual attitudes are inconsistent with their sexual behaviors. Love and family factors influenced early sexual engagement. It is per-ceived that it is responsibility of their parents to support their unplanned pregnancy. The schools’ role is to prevent discrimination of pregnant students and to provide a sex educa-tion program that focuses more on clarifying sexual values, and teaching decision-making and refusal skills. Recommendation were provided particularly on catering school-based services which can help them to appropriately deal with challenges of adolescent preg-nancy and parenthood.